"What happens behind the curtains?" : an exploration of ICU nurses’ experiences of post mortem care - De Swardt, Carien (Department of Health and Rehabilitation Sciences, 2015)
The Aim of the Study: The aim of this study was to explore the experiences of ICU nurses performing post mortem care in an intensive care unit at a private hospital in Cape Town. In addition, the study set out to identify educational needs and to offer recommendations that may address these needs for this sample of ICU nurses. Background to the Study: Post mortem care (care after the death of a human being) is still viewed by contemporary society as a taboo and clandestine aspect of life and is more often avoided both in conversation, writing and thinking. In many hospitals and other healthcare facilities, post mortem care is performed behind closed doors, in which an aura of mystery is created as to what happens to the dead body in this scenario. The nurses’ experience of post mortem care differs from that of other occupational groups (ambulance officers, medical practitioners and police) as the nurse sees the body before and after death and has an established relationship with the person who has died. The practical procedure of post mortem care is widely explored by many authors using various procedural guidelines and/or manuals. However, little is known about the nurse’s experiences of post mortem care. Methodology: A qualitative research design using a descriptive method was used to explore the experiences of a purposive heterogeneous sample of six ICU nurses who were working in an ICU of a private hospital in Cape Town. Data Collection and Analysis: A semi-structured interview which was audio-taped and transcribed verbatim was employed to collect data. Colaizzi’s (1978) seven step inductive method was used to formulate naïve themes. Following participant feedback, three main themes emerged: (i) care of the dead body; detachment and (iii) thanatophobia. Findings: Safeguarding the integrity and physical appearance of the dead body was the major finding and of the utmost priority for the participants in this study. Regardless of how the ICU nurses felt about death, providing professional and quality care to the dead body and the family was seen as significantly important. The ICU nurses, whilst performing post mortem care, experienced detachment from various relationships. This comprised of the ICU nurse detaching him/herself professionally and emotionally from the dead patient, the family and him/herself from the death experience. This ‘unspoken’ experience of thanatophobia became apparent when the ICU nurses were confronted by the reality of their own deaths. Conclusion and Recommendations: These three themes were discussed in relation to the available literature and recommendations put forward for education and nursing practice and further research.